2010
DOI: 10.1016/j.jpain.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Depression Shows Divergent Effects on Evoked and Spontaneous Pain Behaviors in Rats

Abstract: Although it has been accepted that depression and pain are common comorbidities, their interaction is not fully understood. The present study was aimed to investigate the effects of depression on both evoked pain behavior (thermal induced nociception and hyperalgesia) and spontaneous pain behavior (formalin pain) in rats. An unpredictable chronic mild stress (UCMS) paradigm was employed to develop a classical depression. The emotional behaviors were assessed by sucrose preference test, open field test, and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 42 publications
2
61
0
3
Order By: Relevance
“…However, these animals showed increased response in formalin-induced spontaneous nociceptive behaviors [65, 66]. The changes in depressed animals were prevented by chronic antidepressant fluoxetine treatment [65]. In another study, the same authors reported that CUMS-operated animals showed significantly higher pain threshold to thermal stimulus (plantar test) and mechanical stimulus (von Frey test in CCI rats), extending their previous findings [67].…”
Section: Animal Studies Of the Pain-depression Relationshipmentioning
confidence: 68%
See 1 more Smart Citation
“…However, these animals showed increased response in formalin-induced spontaneous nociceptive behaviors [65, 66]. The changes in depressed animals were prevented by chronic antidepressant fluoxetine treatment [65]. In another study, the same authors reported that CUMS-operated animals showed significantly higher pain threshold to thermal stimulus (plantar test) and mechanical stimulus (von Frey test in CCI rats), extending their previous findings [67].…”
Section: Animal Studies Of the Pain-depression Relationshipmentioning
confidence: 68%
“…In two studies from the same lab that employed different depression models (CUMS and OB), depressed animals demonstrated higher pain threshold to thermal stimuli either under normal condition or under CFA-induced chronic pain condition. However, these animals showed increased response in formalin-induced spontaneous nociceptive behaviors [65, 66]. The changes in depressed animals were prevented by chronic antidepressant fluoxetine treatment [65].…”
Section: Animal Studies Of the Pain-depression Relationshipmentioning
confidence: 99%
“…Additionally, food deprivation and social inequality stress decreased the pain perception in formalin-inflammatory pain [51]. The contrary reports included that formalin-inflammatory rats with CMS showed greater nociceptive responses than those without CMS [50]. Rats exposed to chronic restraint stress [52] or SD stress [8,53] developed allodynia or hyperalgesia.…”
Section: Discussionmentioning
confidence: 93%
“…Animal research also incorporated pain-increasing and pain-inhibiting influences of anxiety or depression-like states. Rats subjected to CMS exhibited increased nociceptive thresholds in normal, CFA-inflammation and spinal nerve ligated (SNL)-neuropathic pain conditions [48][49][50]. Additionally, food deprivation and social inequality stress decreased the pain perception in formalin-inflammatory pain [51].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and preclinical studies have demonstrated that altered sensitivity to noxious stimuli, or increased incidence and severity of chronic pain, is associated with a large number of disorders of the central nervous system, including depression Dworkin et al, 1995;Klauenberg et al, 2008;Shi et al, 2010a;Shi et al, 2010b;Terhaar et al, 2010), anxiety disorders (Asmundson and Katz, 2009;Finn et al, 2006;Geuze et al, 2007;Ploghaus et al, 2001;Rivat et al, 2010), multiple sclerosis (Kenner et al, 2007;Olechowski et al, 2009;Solaro et al, 2003) and others. Thus, a passive-avoidance paradigm using air-puff in place of noxious foot-shock may also be preferable for assessment of aversive learning and memory in rodent models of these disorders.…”
Section: Discussionmentioning
confidence: 99%